Pengaruh Social Media Marketing terhadap Keputusan Pengunjung di 3D Stable Palembang - Lusfia, Tiara Kemala; Yunita, Dessy; Mavilinda, Hera Febria (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to determine the influence of Social Media Marketing on visitor decisions at 3D Stable Palembang. The research method used is a quantitative method. The population in this study were all visitors to 3D Stable Palembang using a sample of 100 respondents. The data collection method used in this research is a questionnaire using a 5 point Likert scale. The analysis technique used is multiple linear regression and uses the SPSS application. Based on the results of the analysis, it is concluded that Social Media Marketing simultaneously influences visitors' decisions at 3D Stable Palembang.